Recurrent syncope driven by unique‐variant angina pectoris - Guang Yang; Yanna Lei; Minglong Xin; Wenhu Xu; Guangxian Zhao; Xueying Jin; Meina Piao; Xiang Li; Xian Wu Cheng (Clinical Case Reports, 2024)
Key Clinical Message The patient's vasospastic variant angina manifested as syncope with asymptomatic ischemic episodes, and repeated 24‐h dynamic electrocardiogram and coronary angiography examinations combined with coronary provocation spasm tests were necessary for its diagnosis and management.